The role of spatial and temporal descriptors for neotropical tadpole communities in southern Brazil - Both, Camila; Sole, Mirco; dos Santos, Tiago Gomes [UNESP]; Cechin, Sonia Zanini (Springer, 2009)
We evaluated tadpole communities of temporary and permanent ponds, in order to understand how community richness varies monthly in a subtropical humid climate, to interpret the community structure in relation to biotic and abiotic environmental variables related to the temporary and permanent ponds. The study site was the PrA(3)-Mata Research and Nature Conservation Center, a private reserve in southern Brazil. The climate is classified as Temperate Superhumid, with no dry season. We sampled three temporary and three permanent ponds. We compared the richness of tadpole assemblages of permanent and temporary ponds through individual-based rarefaction curves, and tested for possible differences using a MANOVA test. Tadpole richness was related to temporal environmental descriptors through General Regression Model. Relationships between the tadpole assemblages and possible predictors of their spatial variation were measured using a partial Canonical Correspondence Analysis. Analysis of rarefaction curves indicated higher expected richness for the temporary ponds. The mean values of richness were significantly different between the two hydroperiods across all months. Monthly richness showed the same tendency of variation for both pond types. Only temperature was related to tadpole richness. The pCCA analysis was significant. The most important predictors on the first pCCA axis were vegetation cover, conductivity, depth, and predator diversity. In this study, vegetation cover, conductivity, predator diversity, and water depth explained the spatial variation of tadpoles between ponds, with tadpole richness and diversity being higher in temporary than in permanent ponds. Our results suggest that different spatial-seasonal patterns operating in temporary and permanent ponds are related to maintaining the species diversity of pond-breeding anurans.
Keywords: Anuran; Larvae; Ponds; Community ecology; Phenology; Spatial distribution